Corpos encarnados análise das narrativas escritas para crianças acervo do PNBE/2012 - Sampaio, Lenise Oliveira Lopes (2014)
The focus of this thesis is the analysis of images and narratives which present children s bodies. Special attention is given to the body markers that are in words in a strict connection between sema (language) and soma (body) These narratives as I discuss in the thesis, bring within them seeds that may (or may not) mark, model, alienate or liberate the children s bodies so that they may exercise in full their physical, mental and intellectual capacities as defined in the National Educational Low 1996. Literary production per se is included in the field of Cultural Studies as it is a production of human art. The state of art constructed as theoretical inputs for this research is of a multidisciplinary character, and covers the fields of knowledge in the areas of Sociology, Anthropology, Philosophy, Literary Theory, Infant-juvenile Literature and Infant Education. One must point out the fact that here I show evidence that the productions in the fields of Sociology and Anthropology do not yet consider studies about narratives written for children from the perspective of the child s body, hence originality and theoretic-scientific relevance of this research. I place as the research: what are the meanings of body, feelings and values disseminated through narratives for children and their illustration? The objects of study in this investigation are the materiality and subjectivity of the body present in the narratives written for children and the images of such narratives. This qualitative-quantitative research adopts the documental methodology as scientific procedure with the aim of analysing the content of the data collected constituted of the collection of The National Library for Schools Programme : Reading and Library in Brazilian State Schools/2012 . I defined as my general aim: to analyse the dimensions of Bodies as identities presented in the narratives written for children based on sociological, philosophical and anthropological theories and, as specific objectives: (1) to reveal the findings through categories of analysis such as: race, ethnicity, sex and gender; and (2) identify the cultural and symbolic assets transmitted through the narrative content. This thesis presupposes that the collection of narratives brings out the pluralities, feelings and identifying values of the children s embodiments in the narratives, and reveals contents with meanings and senses in accordance with the multiculturalism and the diversity of standards in Brazilian society. The findings demonstrate that there is a significant opening for the ethnic groups and races in a global sense with the inclusion of foreign narratives. These also present a fluidity and lightness in the bodies, but within hetero-normativity. However, the Brazilian narratives do not take into account the country s diversity and multiculturalism. A very few Brazilian authors present main characters from ethnic groups and different ethnicities that belong to groups in a socially vulnerable state.